Особенности процессов детоксикации у больных раком яичника с разной чувствительностью к препаратам платины = Features detoxification process ovarian cancer patients with different sensitivity to platinum drugs - A. I. Ribin (Kazimierz Wielki University, 2015)
Ribin A. I. Особенности процессов детоксикации у больных раком яичника с разной чувствительностью к препаратам платины = Features detoxification process ovarian cancer patients with different sensitivity to platinum drugs. Journal of Education, Health and Sport. 2015;5(12):686-690. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44820 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A686-690 https://pbn.nauka.gov.pl/works/695937 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive     The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.12.2015. Revised 25.12.2015. Accepted: 29.12.2015.           ОСОБЕННОСТИ ПРОЦЕССОВ ДЕТОКСИКАЦИИ У БОЛЬНЫХ РАКОМ ЯИЧНИКА С РАЗНОЙ ЧУВСТВИТЕЛЬНОСТЬЮ К ПРЕПАРАТАМ ПЛАТИНЫ   FEATURES detoxification process OVARIAN CANCER PATIENTS WITH DIFFERENT Sensitivity to platinum drugs   А. И. Рыбин A. I. Ribin   Одесский национальный медицинский университет Odessa National Medical University, Odessa, Ukraine     Abstract The author, based on the analysis of the results of biochemical tests (ALT, AST, urea) in 33 women diagnosed with ovarian cancer that showed different sensitivity to platinum drugs, revealed that the clinical features and sensitivity to platinum drugs correlates with the activity of enzymes transminirovaniya in the liver and balance this activity. Furthermore, clinical features and sensitivity correlated with the activity of renal excretory function.   Keywords: ovarian cancer, alanintransaminaza, aspartate transaminase, urea.   Реферат Автор на основе  анализа результатов биохимических исследований (АлТ; АсТ, мочевины) у 33 женщин с диагнозом рак яичника, которые проявили разную чувствительность к препаратам  платины, выявил, что особенности клинического течения и чувствительность к препаратам платины коррелируют с активностью ферментов трансминирования в печени и сбалансированностью этой активности. Кроме того, особенности клиники и чувствительности коррелируют с активностью выделительной функции почек.   Ключевые слова: рак яичников, аламинтрансаминаза, аспартаттрансаминаза, мочевина.